Dielectric breakdown properties of hot SF6-CO2 mixtures at temperatures of 300–3500 K and pressures of 0.01–1.0 MPa - Zhong, Linlin; Yang, Aijun; Wang, Xiaohua; Liu, Dingxin; Wu, Yi; Rong, Mingzhe (Physics of plasmas, 2014)
Recently, much attention has been paid to SF6-CO2 mixtures as one of substitutes for pure SF6 gas. In this paper, the dielectric breakdown properties of hot SF6-CO2 mixtures are investigated at temperatures of 300–3500 K and pressures of 0.01–1.0 MPa. Under the assumptions of local thermodynamic equilibrium and local chemical equilibrium, the equilibrium compositions of hot SF6-CO2 mixtures with different CO2 proportions are obtained based on Gibbs free energy minimization. The cross sections for interactions between electrons and neutral species are presented. Some unknown ionization cross sections are determined theoretically using Deutsch–Märk (DM) formalism based on quantum chemistry. Two-term Boltzmann equation is adopted to calculate the electron energy distribution function, reduced ionization coefficient, reduced attachment coefficient, and reduced effective ionization coefficient. Then the reduced critical electric field strength of mixtures, corresponding to dielectric breakdown performances, is determined when the generation and loss of electrons are balanced. Finally, the influences of temperature, pressure, and CO2 proportion on the reduced critical electric field strength are studied. It is found that a large percentage of CO2 can obviously reduce concentrations of high-energy electrons. At temperatures above 1750 K, an addition of CO2 to SF6 gas can enhance dielectric breakdown performances. However, at low temperatures, too much CO2 added into mixtures can reduce dielectric breakdown abilities. In addition, increasing gas pressure can improve dielectric breakdown performances. But the influence will be no more significant if pressure is over 0.8 MPa.